Neuronal Representation of 3-D Space in the Primary Visual Cortex and Control of Eye Movements. (August 2015) - Alekseenko, Svetlana V.
The aim of this article is to consider the correlations between the structure of the primary visual cortical area V1 and control of coordinated movements of the two eyes. Using the anatomical data available, a schematic map of 3-D space representation in the layer IV of area V1 containing only monocular cells has been constructed. The analysis of this map revealed that binocular neurons of V1, which are formed by convergence of monocular cells, should encode the absolute disparity. Participation of monocular and binocular neurons of V1 in the control of convergence, divergence, and version eye movements is discussed. It is proposed that synchronous contraction of corresponding extraocular muscles of both eyes for vergence might be ensured by duplicated transmission of information from the central part of retina to visual cortex of both hemispheres.